THE GREAT ESCAPE - Do, Anh; Ley, Jeremy; Ji, Annie (Crows Nest, NSW : Allen & Unwin, 2019)
I held onto the bars of the truck and howled to my dogs as they fell further and further behind. Sunrise, Brutus, Zip, Nosey and Tiny all ran as hard as they could, but there was no way they could keep up... After four years alone in the wild, Gwen is overjoyed to see another person. But when she is thrown into the back of a van and stolen away to a prison camp, things don't look good. How will her pack find her? Where is her human family? Will the other kids in the camp be friends or enemies? Luckily, Eagle is fast, the dogs are brave, and bars and fences are no match for the one and only Wolf Girl!
Keywords: Human-animal relationships -- Juvenile fiction; Wilderness areas -- Juvenile fiction; Wilderness survival -- Juvenile fiction; Dogs -- Juvenile fiction; Wolves -- Juvenile fiction; Ability -- Juvenile fiction